Machining parameters in WEDM of EN31 steel using Taguchi technique optimization. (2022) - R, Kamalakannan; G M, Pradeep; T, NaveenKumar; M, Elango
Abstract: Wire electrical discharge machining (WEDM) is often used in the machining of conductive materials when precision is important. The current study looked at wire-cut electric discharge machining of EN31 steel. Taguchi's L27 orthogonal array was used to finish the investigation using various amounts of input parameters. This method was used to determine the optimal parameter combination. The experimental findings show that the machining model is correct, and Taguchi's approach meets the practical requirements. Surfaces having micro cracks and porosity, as well as poor surface quality, are produced by rough machining with WEDM. Finish machining yields a better surface finish (Ra) but at a slower rate (MRR). As a result, the Taguchi approach's purpose is to improve MRR while lowering Ra. To check the performance measures in terms of Surface Roughness, control parameters such as voltage applied, pulse width, pulse interval, and speed were used.